2005
DOI: 10.1091/mbc.e04-09-0833
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Rereplication Control inSaccharomyces cerevisiaeResults in Extensive DNA Damage

Abstract: To maintain genome stability, the entire genome of a eukaryotic cell must be replicated once and only once per cell cycle. In many organisms, multiple overlapping mechanisms block rereplication, but the consequences of deregulating these mechanisms are poorly understood. Here, we show that disrupting these controls in the budding yeast Saccharomyces cerevisiae rapidly blocks cell proliferation. Rereplicating cells activate the classical DNA damage-induced checkpoint response, which depends on the BRCA1 C-termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(96 citation statements)
references
References 65 publications
8
88
0
Order By: Relevance
“…The incorporation of EdU into distinct foci was seen in 9% of atxr5,6 nuclei, but was rarely observed in wild type (<0.1%, Fig regions [i.e., being more abundant in pericentromeric heterochromatin than in the arms of the chromosomes (12)], it should be noted that processes other than overreplication, such as replication-dependent DNA repair, could also account for or contribute to this pattern of EdU incorporation. Overreplication is known to lead to genomic instability and DNA damage, including double-strand breaks (24)(25)(26)(27)(28). Consistent with this observation, many DNA damage-response genes, including BRCA1, PARP1, CYCB, and RAD51 (Fig.…”
Section: Significancesupporting
confidence: 64%
“…The incorporation of EdU into distinct foci was seen in 9% of atxr5,6 nuclei, but was rarely observed in wild type (<0.1%, Fig regions [i.e., being more abundant in pericentromeric heterochromatin than in the arms of the chromosomes (12)], it should be noted that processes other than overreplication, such as replication-dependent DNA repair, could also account for or contribute to this pattern of EdU incorporation. Overreplication is known to lead to genomic instability and DNA damage, including double-strand breaks (24)(25)(26)(27)(28). Consistent with this observation, many DNA damage-response genes, including BRCA1, PARP1, CYCB, and RAD51 (Fig.…”
Section: Significancesupporting
confidence: 64%
“…First, if replication controls are highly redundant, the probability that a cell will spontaneously acquire the multiple disruptions needed to induce re-replicate will be extremely small. Second, we and others have shown that cells undergoing overt re-replication experience extensive inviability (Jallepalli et al, 1997;Yanow et al, 2001;Wilmes et al, 2004;Green and Li, 2005) or apoptosis (Vaziri et al, 2003;Thomer et al, 2004), making cell death a more likely outcome than genomic instability or tumorigenesis.…”
Section: Levels Of Re-replication Likely To Contribute To Genomic Insmentioning
confidence: 85%
“…Rereplication is a potential source of genomic instability both because it produces extra copies of chromosomal segments and because it generates DNA damage and/or replication stress Zhu et al, 2004;Archambault et al, 2005;Green and Li, 2005). Re-replication has also been potentially linked to tumorigenesis by the observation that overexpression of Cdt1, which can contribute to re-replication (reviewed in Blow and Dutta, 2005), can transform NIH3T3 cells into tumorigenic cells (Arentson et al, 2002).…”
Section: Levels Of Re-replication Likely To Contribute To Genomic Insmentioning
confidence: 99%
“…Almost all cells induced to rereplicate die, even if the CDC6 inducing rereplication is turned off quickly after induction. Green and Li (2005) have shown that rereplication leads to double-strand DNA breaks, presumably the cause of the lethality.…”
Section: Discussionmentioning
confidence: 99%